Assessing farm-level agricultural sustainability using site-specific indicators and sustainable livelihood security index: Evidence from Vaishali district, India. Issue 5 (19th October 2016) - Sajjad, Haroon; Nasreen, Iffat
Abstract: Agriculture is the backbone of the Indian economy, where two-thirds of the rural community depend on agriculture for their employment. Sustainable agriculture, with its ability to remain productive in the long term, may help ensure food security for communities in India. This article attempts to examine agricultural sustainability among farming communities in Vaishali, India. In order to evaluate agricultural sustainability, we followed the sustainable livelihood security index (SLSI) approach, which is characterized by three interacting components indices (ecological security, economic efficiency, and social equity). We collected data concerning the domains of agricultural sustainability from 959 farmers' households. The analysis revealed that agricultural sustainability among the farmers decreased as the size of land holdings decreased. Nearly one-third of the total sampled farmers had low agricultural sustainability. Regression analysis showed that economic efficiency and social equity influenced the agricultural sustainability. The SLSI approach helped to identify priorities for attaining farmers' agricultural sustainability.